THE MAIN TYPES OF NONVERBAL COMMUNICATION ENGLISH AND UZBEK LANGUAGES - Shukurova Nafosat Rustamovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provided English and Uzbek nonverbal communication methods along with some examples. The improvement of understanding regarding communication without language is the goal of this article. In addition, several benefits and drawbacks were listed for the readers' better comprehension.